Further evidence of the prognostic role of pretreatment levels of CA 19-9 in advanced pancreatic cancer - Saad, Everardo D. (2010)
OBJECTIVE: We and others have previously suggested that pretreatment levels of CA 19-9 correlate with overall survival (OS) among patients with advanced pancreatic cancer treated with gemcitabine. We sought to confirm the prognostic role of the pretreatment level of CA 19-9 in patients with advanced pancreatic cancer treated with chemotherapy. METHODS: We retrospectively identified 50 patients with locally advanced or metastatic pancreatic cancer treated in the first-line with single-agent gemcitabine or combinations. Patients could also have received second-line treatment. Kaplan-Meier estimates of OS were compared with the log-rank test, and multivariate analysis was done using the Cox model. RESULTS: Twenty-seven patients were female with a mean age of 64.3 years, and 82% were metastatic upon diagnosis. The median OS for the entire sample was 11 months, and the median CA 19-9 level was 542 U/mL. Significant predictors of OS in univariate analyses were the first-line use of combined chemotherapy (p=0.006) and use of erlotinib in any line (p=0.002), with borderline significance for pretreatment levels of CA 19-9 (p=0.052). In multivariate analysis, only use of erlotinib (p=0.003) and pretreatment CA 19-9 level (p=0.026) were significantly associated with OS. CONCLUSION: Our study lends further support to use of the pre-chemotherapy level of CA 19-9 as a prognostic indicator in clinical practice and as a stratification factor in clinical trials. The association between erlotinib use and OS may have been biased by patient selection, notwithstanding the positive results from a previous randomized trial.